Tumor necrosis serves as an important pathological characteristic of stage I–II colon cancer - Shuhui Dong; Jin Xu; Mingshan Li; Guangyi Xiong; Ruilin Wang (Indian Journal of Pathology and Microbiology)
Background: The long-term prognosis of colon cancer patients remains little changed with relatively high mortality and morbidity. Since the most widely used prognostic parameter TNM staging system is less satisfactory in predicting prognosis in early-stage cancers, numerous clinicopathological factors, including tumor necrosis, have been proposed for prognosis stratification, but substantial evidences are still lacking for early-stage colon cancer. Materials and Methods: In the retrospective study, a total of eligible 173 stage I–II colon cancer patients, who received tumor radical resection and lymphadenectomy in the local hospital between January 1, 2010, and December 31, 2018, were enrolled for analyzing the prognostic role of tumor necrosis. The primary endpoints included 5-year overall survival (OS) and progression-free survival (PFS). Results: The median follow-up of enrolled early-stage colon cancer patients was 58.3 months. The 2-year and 5-year OS rates were 88.3% and 68.2%, respectively, and the 2-year and 5-year PFS rates were 85.6% and 62.7%, respectively. Seventy-eight patients (45.1%) were diagnosed with tumor necrosis by pathological examination. Demographic analysis revealed a significant association of tumor necrosis with larger tumor size and a marginal association with vascular invasion. Kaplan–Meier survival curves demonstrated that tumor necrosis was associated with worse OS (log-rank P = 0.003) and PFS (log-rank P = 0.002). The independent unfavorable prognostic effect of tumor necrosis was further validated in univariate and multivariate Cox regression analysis (hazard ratio = 1.91 (1.52–2.40), P = 0.004). Conclusions: The current study confirmed the independent prognostic role of tumor necrosis from pathological review in early-stage colon cancer patients. This pathological criterion promises to help in identifying high-risk subgroup from early-stage colon cancer patients, who may benefit from strict follow-up and adjuvant therapy.